The Effectiveness of Implementation English Listening Lesson Library Online (ELLLO) Application to Improve Students' Listening Skill at MA Mathalibul Huda Mlonggo - Diva Dyah Lestari; Aprilia Riyana Putri (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
This study investigated the effectiveness of implementation English Listening Lesson Library Online (ELLLO) application in improving students’ listening skill at MA Mathalibul Huda Mlonggo. The study applied a one-group-pre-test and post-test experimental design, using population students grade XI at Mathalibul Huda Mlonggo. It used purposive sampling with 30 students from class XI IPS 5 paticipated as the research sample. Students’ listening abilities were assessed before and after the implementation of ELLLO application used worksheets containing multiple-choice questions. The results clearly showed that students got better at listening after using the ELLLO application, with their scores improving from before to after the test. The data analysis backed this up, proving that the app really made a difference. It can be seen in statistical analysis that t-obtained (2.298) was higher than t-critical (2.045) and significant (0.029) was lower than (α < 0.05). The finding demonstrated that the integration of technology-based resources such as ELLLO application can improve listening proficiency and provide more engaging English learning experiences. The study suggests that ELLLO application is one of effectiveness digital tools for supporting English listening and recommends in using this application to face the challenges in English education and to optimize students’ language learning outcomes particularly in listening skill.